Analisis del Software Sagitario aplicando la Norma ISO 27000 de la Librería Cristiana "La Colmena" de la ciudad de Babahoyo. - Arteaga Madrid, Genesis Madelein (2024)
The following work, titled Analysis of the Sagitario Software applying the ISO 27000 Standard of the Christian bookstore "La Colmena" in the city of Babahoyo, maintains the objective of evaluating the security of the Sagittarius Software used in this bookstore through the framework of the ISO 27000 Standard. This bookstore is a small Christian company located in the city of Babahoyo, where various sensitive data related to its commercial activity is managed. An assessment of the information assets, associated risks and potential weaknesses of the Sagitario software will be carried out. Based on the results, prioritized corrective actions will be implemented to strengthen information security and ensure compliance with ISO 27000. In addition, a program of continuous monitoring and improvement will be established to ensure that the Christian bookstore "La Colmena" maintains a secure environment for its data. This project will not only contribute to improving information security at "La Comena", but will also serve as a relevant case study for other similar organizations looking to strengthen their cybersecurity posture.